2016
DOI: 10.1016/j.rpped.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Ângulo de fase e critérios da Organização Mundial de Saúde na avaliação do estado nutricional em crianças com osteogênese imperfeita

Abstract: Children with osteogenesis imperfecta have a nutritional risk detected by the phase angle, which is a useful tool for nutritional screening. The calculation result could help in the diet therapy of patients with osteogenesis imperfecta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Main compartments analyzed were (a) skeletal muscle mass, body fat mass, and fat-free mass, and (b) body water (intracellular; extracellular; total; body water ratio, ECW/TBW), body cell mass, and phase angle (PhA). Reference values of mean PhA in healthy children were obtained from the Nogueira and Bosy-Westphal studies [ 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Main compartments analyzed were (a) skeletal muscle mass, body fat mass, and fat-free mass, and (b) body water (intracellular; extracellular; total; body water ratio, ECW/TBW), body cell mass, and phase angle (PhA). Reference values of mean PhA in healthy children were obtained from the Nogueira and Bosy-Westphal studies [ 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…PhA is expressed by the arc tangent of the reactance and resistance and is used as an indicator of nutritional status in different patients, such as malnourished children and patients undergoing gastrointestinal surgery. [17][18] Previous studies have found a direct association between PhA and cardiorespiratory tness in critically ill pediatric patients, 19 HIV-infected children, 20 and malnourished children, 21 and only one study with healthy children. 22 Its usage is endorsed as an indicator for prognosis in children clinical practice, 23 and when correlated with anthropometric data -weight and height -in patients that underline nutritional risk, its subsids a great screening tool.…”
Section: Introductionmentioning
confidence: 99%
“…Um dos parâmetros obtido através dos resultados da BIA é o Ângulo de Fase (PhA). O PhA é o arco tangente da reactância pela resistência (Xc/R), ou seja, é obtido a partir da avaliação de BIA por meio das medidas diretas dos componentes de R e Xc, e, se usado como indicador de estado nutricional e massa celular corporal diminui consideravelmente os erros de análise pela BIA (PILEGGI; SCALIZE; CAMELO JUNIOR, 2016;SCHIESSER et al, 2009).…”
Section: Introductionunclassified